If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -29 = 5x + -7 Reorder the terms: -29 + 6x = 5x + -7 Reorder the terms: -29 + 6x = -7 + 5x Solving -29 + 6x = -7 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -29 + 6x + -5x = -7 + 5x + -5x Combine like terms: 6x + -5x = 1x -29 + 1x = -7 + 5x + -5x Combine like terms: 5x + -5x = 0 -29 + 1x = -7 + 0 -29 + 1x = -7 Add '29' to each side of the equation. -29 + 29 + 1x = -7 + 29 Combine like terms: -29 + 29 = 0 0 + 1x = -7 + 29 1x = -7 + 29 Combine like terms: -7 + 29 = 22 1x = 22 Divide each side by '1'. x = 22 Simplifying x = 22
| 15x-8x=40+9 | | 5p^2-6=7p | | -10-3c=10+9c | | 6x+4=8x-7(-x+3)-4x | | -11x+43=-34 | | 2x^67=9r | | 12-x=-32 | | 22-5r=2r | | x^2+x=4.27 | | 6p+5=17 | | 2(x^2-7x+21)=0 | | 502.4=3.14(4)h | | Y-x=-9 | | 30+x=167 | | .5(2n-3)-.1=.4(6+2n) | | 5*8+6y=94 | | 15-8x=49 | | 8q-q=14 | | 1.7+7n=9.5-4n | | 3(5x-9)=-2(6-2x)+2 | | 5b-27-23b=7 | | -5x-15=(-30) | | 25x+5*5=125 | | 2p^2-2p-40=0 | | -(4+a)=3a | | 4(3-5x)=-5(3x+3) | | 9t-3=15 | | -11=9-5 | | 180=9x+1+8x+9 | | 3m-2n-4=42 | | 4x+6=2.727272 | | 2x+22=3x+2 |